Ali Baba and the forty thieves - Rollason, Jane (London York press, 2020)
Ali Baba is a woodcutter. one day he is in the forest. he hears a noise it is fortybthieeves on forty horses, they stop in front of a big rock, open door, please open they say and a door opens the rock, does Ali Baba open the door in the rock? what does he find?
English stories
1
Keywords: English stories